On the preparation and characterization of thin NiTi shape memory alloy wires for MEMS - Riccardo Casati; Maurizio Vedani; Syed A. M. Tofail; Calum Dikinson; Ausonio Tuissi (Fracture and Structural Integrity)
Shape memory alloy (SMA) wires are employed as actuators in small devices for consumer electronics, valves and automotive applications. Because of the continued miniaturization of all the industrial products, nowadays the tendency is to produce MEMS (micro electromechanical systems). Among the most promising functional MEMS materials, the thin SMA wires that are offering a rapid actuating response with high power/weigh ratio of the material, are attracting a world wide interest. This paper is aimed at showing the production process and the characterizations of thin NiTi shape memory wires. The activity was focused on drawing procedure and on functional and TEM characterizations of the final products. In particular, it was evaluated the performance of the SMA wires for actuators in terms of functional fatigue and thermo-mechanical properties by means of an experimental apparatus design ad hoc for these specific tests